(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Artemisinin and its derivatives such as artesunate, arteether and artemether are the primary and effective treatment of choice as per WHO malaria treatment guideline for the treatment of severe malaria although various endemic countries are using quinine for the treatment of severe malaria. The objective of this meta-analysis was to evaluate the efficacy and safety of artemisinin and its derivatives compared with quinine as parenteral antimalarial therapy for treating severe malaria in children. From the year 1990 to the year 2015, studies were identified using database searches, citation searches of selected articles. The electronic databases searched engines: Pubmed, Web of Science, Global Health, Medline & Cochrane review of Journals up to April 2015. We selected published randomized controlled clinical trials (RCTs) information comparing artemisinin derivatives with quinine and route of administration was either intravenous or intramuscular for treatment of severe malaria in paediatric population as per WHO malaria treatment guideline, any gender, age group up to 15 years of children who were diagnosed with confirmed malaria by RDT or slide test. The primary outcome was efficacy in terms of parasite clearance time (PCT) and fever clearance time (FCT) in paediatrics population. The secondary outcome was the mortality, coma resolution time (CRT) and neurological sequelae at the time of discharge in the paediatric population. We assessed identified articles on the basis of clinical trial eligibility, the risk of bias and extracted data as per objective of this research for the desired outcomes. We measured 95% confidence interval by the using of REVMAN software version 5.3 for meta-analysis and summarized the collected data on the basis of characteristics of inclusion criteria of articles such as risk ratio (RR) for dichotomous outcomes and mean difference (MD) for continuous outcomes. We included total 17 RCTs, enrolling 7220 paediatric patients who were suffering from severe or complicated malaria and these trials were conducted in various countries in the world. Artemisinin derivatives showed mean PCT (MD -8.53 hours, 95% CI -9.44 to -7.62) and mean FCT (MD -9.42 hours, 95% CI -11.12 to -7.71) shorter and statistically significant (P<0.00001) as compared with quinine therapy. We evaluated secondary outcomes mortality, mean coma resolution time (CRT) and the risk of neurological sequelae at the time of discharge in paediatric malaria patients which was observed; (RR 0.82, 95% CI 0.72 to 0.93; 17 trials, 7220 participants, P=0.002), (MD -5.37 hours, 95% CI -7.70 to -3.05; nine trials, 591 participants, P<0.00001) and (RR 1.07, 95% CI 0.89 to 1.28; nine trials, 5939 participants, P=0.49), respectively. This meta-analysis of RCT addresses the evidence for various aspects in the treatment of severe malaria in the paediatric population although limitation of availability of published information in studies furthermore research on paediatric malaria population is required to overcome from challenges drug resistance, patient compliance and less adverse effect.